OPTIMALISASI KEBIASAAN BARU HIDUP BERSIH DAN SEHAT PASCA PANDEMI COVID-19 PADA PEKERJA DI KAWASAN WISATA PANTAI CIMPAGO KOTA PADANG - Ayulia Fardila Sari ZA; Shelvy Haria Roza (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Padang Beach Tourism Area is one of the vital areas in the Adaptation of New Habits period because it has the potential to cause many people to gather in the same place. Based on preliminary studies, there were many workers who do not wear masks and keep their distance. Efforts were needed to increase worker compliance with health protocols and the Adaptation of New Habits in preventing Covid-19. The aim of this activity was to increase the knowledge of workers in the Padang Coast tourist area regarding the implementation of Adaptation to New Habits after the Covid-19 pandemic. The community service method used was health education. The participants in the counseling were 2 employees of the Padang City Tourism Office as well as 19 cleaners and a SAR team who worked at Padang Beach. The activity phase begins with preparation, implementation of counseling and evaluation. The counseling held at the Cimpago Beach parking lot, Padang City. Result of the activity, an increase in participants' knowledge about new habits after the Covid-19 pandemic was obtained based on an increase in pre-test and post-test scores. Apart from that, there was a commitment from the Padang City Tourism Office to ensure that officers working at Padang Beach were able to be examples in implementing new habits at tourist locations. To ensure this, posters and leaflets were given on how to wash hands, how to wear masks, and how to behave in a healthy and clean manner outside and inside the house. It can be concluded that outreach activities are able to increase participants' knowledge about new habits after the Covid-19 pandemic. It is hoped that outreach participants can convey the information they have obtained to business actors and visitors in the Padang Beach tourist area.